Perbandingan Konstruksi Dan Biaya Untuk Struktur Perkerasan Lentur, Kaku Dan Paving Blok Pada Jalan Pantai Utara Flores - Mahardika, Vera; Mudiyono, Rachmat; Soedarsono, Soedarsono (Universitas Dr. Soetomo, 2021)
Flexible, rigid, and paving block pavements can be used as alternative roads because the soil conditions on the Pantai Utara Flores road are rocky soil with a relatively high CBR so that the most important role in withstand load is subgrade. The purpose of the Comparison of Construction and Costs for Flexible, Rigid, and Paving Block Pavement Structures on Jalan Pantai Utara Flores is to know which one most effective and efficient when viewed from the traffic load with each pavement using the Bina Marga method, AASHTO , and Direktorat Jendral Bina Marga. Jalan Pantai Utara Flores is access to Komodo Labuan Bajo airport which is a Class I road, rocky land with a relatively high CBR, rainfall of Labuan Bajo is relatively low, LHR in Labuan Bajo is relatively small, besides Labuan Bajo is a tourist area that should be supported by road access that has driving comfort so the suitable pavement structure for Jalan Pantai Utara Flores is flexible pavement. Meanwhile, based on the recapitulation of the analysis results, the cost of flexible pavement is Rp. 28,793,604,705,600, the cost of a rigid pavement is Rp. 34,218,430,585,828 and the cost of paving block pavement is Rp. 17,410,645,080,000 so it can be seen that the paving block pavement is most economical, but the paving block pavement structure has a very uncomfortable driving comfort besides that the paving block pavement structure cannot be passed by vehicles at high speed so that the paving block pavement structure is more suitable for controlling speed of vehicles such as roads in crowded urban areas and residential roads.